Genresignaturen. En retorisk nydannelse - Nyboe, Jacob Ølgaard (Passage - Tidsskrift for litteratur og kritik, 2016)
Jacob Ølgaard Nyboe: “Genre Signature. A Rhetorical Neologism ” The article introduces the notion of genre signature defined as a creative, unique or deliberately misguiding genre label. It is argued that the genre signature holds a great rhetorical potential in negotiating the position as well as the interpretation of a literary work. The phenomenon is examined through analyses of contemporary Danish literature and is viewed in the context of Rhetorical Genre Studies (RGS), new literary tendencies and media reception.